Finite element solutions with Walsh series and wavelets - de Freitas, J.A. Teixeira; Castro, L.M.S. Santos (Computer Assisted Methods in Engineering and Science, 1997)
Walsh series and wavelets are nowadays widely applied in digital processes. Their use as approximation functions in a hybrid.mixed finite element formulation for elastic-plastic structural analysis is presented. This formulation is based on the direct approximation of the stress, displacement and plastic multiplier fields in the domain of the finite elements. The displacements on the boundary of the clements are also ap-aproximated independently. The essential characteristics and properties of the Walsh and wavelet approximation functions are reviewed. The performances achieved in the different solution phases of elastic and elastoplastic problems are illustrated with numerical applications.